Estudo da distribuição das pressões plantares em crianças obesas: efeitos de um programa de intervenção - Filippin, Nadiesca Taisa (Universidade Federal de São Carlos, 2007)
The purpose of this study was to assess the effects of a weight reduction program on the plantar pressure behavior during standing and walking of obese children. Thirty children, divided into three groups (obese experimental group, obese control group and non obese group), both genders, aged between nine and eleven years old volunteered to this study. The data were collected before and after a weight reduction program with duration of three months. The evaluations included static footprints and plantar pressure variables under six areas of the foot during standing and walking using the Pedar System (Novel GMBh). The results revealed that there was a decrease in the pressures under the midfoot area for the experimental group after the training program, but plantar pressure changes were not observed under other foot areas. An increase in the pressure-time integral was observed after training for the same obese group. In addition, the obese children presented greater contact areas and pressures when compared to non-obese, which can indicate increased risk of injuries due to the excessive load supported by the lower limbs of the obese children. However, the body weight was only poorly related to the plantar pressures, indicating that others factors may interfere on pressure distribution patterns. The correlations between the variables in the midfoot area indicated that it is not possible to assess the dynamic function of the feet from static measures, mainly in obese children, since the excess of adipose tissue in the feet and the medial arch changes may not allow the appropriate interpretation of these measures. Because the plantar pressures measured in this study were not sensitive enough to the training program of three months and, therefore were less influenced by it, the planning of weight reduction programs of longer durations and applied as early as possible is recommended, in order to promote important changes in the plantar pressure behavior and, consequently, to prevent structural and functional disorders in the children s feet.
A study on the plantar pressure distribution in obese children: effects of a weight reduction program
Keywords: Biomecânica; Obesidade nas crianças; Pressão plantar; Plantar pressure; Obesity control; Children; Biomechanic; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL